Appraisal of disease‐specific benefits of minimally invasiveness in surgery of breast cancer liver metastases. Issue 7 (9th September 2019) - Ratti, Francesca; Serenari, Matteo; Zanello, Matteo; Prosperi, Enrico; Cipriani, Federica; Ercolani, Giorgio; Jovine, Elio; Cescon, Matteo; Aldrighetti, Luca
Abstract: Background: The primary endpoint of this study is to analyze short term benefit of laparoscopic approach (minimally invasive liver surgery [MILS]) over the open techniques in patients submitted to surgery for breast cancer liver metastases (BCLM) within a disease‐specific perspective. Material and Methods: A group of 30 patients who underwent laparoscopic liver resection for BCLM constituted the Study group (MILS group) and was matched in a ratio of 1:2 with patients who underwent open surgery for BCLM (Open group, constituting the Control group). Results: MILS approach resulted in a statistically significant lower blood loss (150 vs 300 mL; P < .05). The rate of postoperative complications was similar (13.3% and 16.6% in the MILS and Open groups, respectively). MILS approach was associated with a shorter length of postoperative stay (4 ± 2 days) compared with the Open group (7 ± 3 days), allowing a faster return to adjuvant treatments. Both MILS and open groups showed adequate oncological radicality, with comparable long‐term results. Conclusion: MILS approach to BCLM represents the optimal instrument to obtain an adequate disease clearance in the selected group of patients candidates to surgery: the type of procedure (minor resections for limited hepatic disease) and characteristics of patients contribute to enhance the feasibility and the benefits of the laparoscopic technique.